Comparison of native and non-native phone imitation by English and Spanish speakers - Olmstead, Annie J.; Viswanathan, Navin; Aivar, M. Pilar; Manuel, Sarath (Frontiers in Psychology, 2013)
Experiments investigating phonetic convergence in conversation often focus on interlocutors with similar phonetic inventories. Extending these experiments to those with dissimilar inventories requires understanding the capacity of speakers to imitate native and non-native phones. In the present study, we tested native Spanish and native English speakers to determine whether imitation of non-native tokens differs qualitatively from imitation of native tokens. Participants imitated a [ba]–[pa] continuum that varied in VOT from −60 ms (prevoiced, Spanish [b]) to +60 ms (long lag, English [p]) such that the continuum consisted of some tokens that were native to Spanish speakers and some that were native to English speakers. Analysis of the imitations showed two critical results. First, both groups of speakers demonstrated sensitivity to VOT differences in tokens that fell within their native regions of the VOT continuum (prevoiced region for Spanish and long lag region for English). Secondly, neither group of speakers demonstrated such sensitivity to VOT differences among tokens that fell in their non-native regions of the continuum. These results show that, even in an intentional imitation task, speakers cannot accurately imitate non-native tokens, but are clearly flexible in producing native tokens. Implications of these findings are discussed with reference to the constraints on convergence in interlocutors from different linguistic backgrounds.